Neue paläarktische Arten aus der Gattung Aprionus Kieffer, 1894 (Diptera: Cecidomyiidae, Lestremiinae). - Mamaev, Boris M.; Jaschhof, Mathias (Contributions to Entomology = Beiträge zur Entomologie, 1997)
The following Palaearctic species of lestremiines of the genus Aprionus Kieffer are described as new to science: A. lapponicus Jasch. & Mam. sp. n., A. stylatus Mam. & Jasch. sp. n., A. paludosus Jasch. & Mam. sp. n., A. indictus Mam. & Jasch. sp. n., A. separatus Mam. & Jasch. sp. n., A. caucasicus Mam. & Jasch. sp. n., A. laricis Mam. & Jasch. sp. n., A. pommeranicus Jasch. & Mam. sp. n. Nomenclatural Actscaucasicus Mamaev & Jaschhof, 1997 (Aprionus), spec. n.indictus Mamaev & Jaschhof, 1997 (Aprionus), spec. n.lapponicus Jaschhof & Mamaev, 1997 (Aprionus), spec. n.laricis Mamaev & Jaschhof, 1997 (Aprionus), spec. n.paludosus Jaschhof & Mamaev, 1997 (Aprionus), spec. n.pommeranicus Jaschhof & Mamaev, 1997 (Aprionus), spec. n.separatus Mamaev & Jaschhof, 1997 (Aprionus), spec. n.stylatus Mamaev & Jaschhof, 1997 (Aprionus), spec. n.